Ten-Year Change in Neighborhood Socioeconomic Deprivation and Rates of Total, Cardiovascular Disease, and Cancer Mortality in Older US Adults. Issue 12 (22nd August 2018) - Xiao, Qian; Berrigan, David; Powell-Wiley, Tiffany M; Matthews, Charles E
Abstract: Low neighborhood socioeconomic status has been linked to adverse health outcomes. However, it is unclear whether changing the neighborhood may influence health. We examined 10-year change in neighborhood socioeconomic deprivation in relation to mortality rate among 288, 555 participants aged 51–70 years who enrolled in the National Institutes of Health-AARP Diet and Health Study in 1995–1996 (baseline) and did not move during the study. Changes in neighborhood socioeconomic deprivation between 1990 and 2000 were measured by US Census data at the census tract level. All-cause, cardiovascular disease, and cancer deaths were ascertained through annual linkage to the Social Security Administration Death Master File between 2000 and 2011. Overall, our results suggested that improvement in neighborhood socioeconomic status was associated with a lower mortality rate, while deterioration was associated with a higher mortality rate. More specially, a 30-percentile-point reduction in neighborhood deprivation among more deprived neighborhoods was associated with 11% and 19% reductions in the total mortality rate among men and women, respectively. On the other hand, a 30-point increase in neighborhood deprivation in less deprived neighborhoods was associated with an 11% increase in the mortality rate among men. Our findings support a longitudinal association between changing neighborhood conditions and mortality.